Impact of different spacer filament geometries on concentration polarization control in narrow membrane channel - Ahmad , A.L.; Lau, K.K.; Abu Bakar, M.Z. (Elsevier B.V., 2005)
Fluid flow condition adjacent to the membrane interface plays a vital role in controlling mass transfer and concentration polarization mechanism across the membrane. Thus, optimized design of spacer is crucial to deter the formation of concentration polarization layer while maintaining certain degree of pressure drop. The main objective of this paper is to integrate the permeation properties in commercial CFD codes FLUENT 6 for simulating flow conditions and permeation properties in the spacer-filled narrow membrane channel. Turbulence model have been integrated in the solution of time averaged incompressible flow equations. Different types of spacer filament geometries have been analyzed and evaluated to determine their ability in controlling concentration polarization and pressure drop. This study has also demonstrated the dependency of filament geometries performance on feed Reynolds number. This method potentially offers faster approach to determine the optimum geometries of spacer filament in the narrow membrane channel if compared with experimental methods.